KERJASAMA INDONESIA DENGAN INTERNATIONAL LABOUR ORGANIZATION (ILO) MELALUI PROGRAM IPEC DALAM MENEKAN PEKERJA ANAK SEKTOR TEMBAKAU DI INDONESIA TAHUN 2014-2018 - Baby Anita Eka Putri (2020)
The phenomenon of child labor in Indonesia from year to year becomes a very complex issue, which in 2014 the level of child labor in Indonesia reached the highest rate. Indonesia is the country with the largest tobacco industry in Asia, where there are certainly child laborers working in the tobacco industry, mainly in the provinces of East Java and West Nusa Tenggara. The Government of Indonesia together with one of the international labor organizations under the auspices of the United Nations International Labor Organization (ILO) cooperated in realizing the elimination of child labor in the tobacco sector in Indonesia from 2014 to 2018 through a program established by the ILO namely the International Program Elliminate of Child Labor (IPEC). This approach is qualitative, the type of research used is descriptive analysis. The sources used are primary and secondary data obtained from interviews, literature studies, and primary data from the ILO and KPAI offices. Data will be analyzed using the theory of neo - liberalism and International Organization theory. Based on the data analysis carried out, it was concluded that Indonesia's collaboration with the ILO in providing assistance through the IPEC program to eliminate child labor in Indonesia has resulted in 2 ILO conventions and the new regulation and policies of the Indonesian government.